Estimation of Source-Filter Interaction Regions Based on Electroglottography - Palaparthi, Anil; Maxfield, Lynn; Titze, Ingo R. (Journal of voice, 2019)
Source-filter interaction is a phenomenon in which acoustic airway pressures influence the glottal airflow at the source (level 1) and the vibration pattern of the vocal folds (level 2). This interaction is most significant when dominant source harmonics are near airway resonances. The influence of acoustic airway pressures on vocal fold vibration (level 2) was studied systematically by changing the supraglottal vocal tract length in human subjects with tube extensions. The subjects were asked to perform fundamental frequency (fo) glides while phonating through tubes of various lengths. An algorithm was developed using the quasi-open quotient extracted from the electroglottograph. Regions of sudden vocal fold vibration pattern change due to source-filter interaction were inferred from contact area changes. The algorithm correctly identified 89% of male and 84.8% of female quantal changes in contact pattern associated with interactions between source harmonics and formants during ascending glides. During the descending glides, the algorithm correctly identified 84% of male and 81.1% of female quantal changes in contact pattern. These results are in comparison with those obtained from the fo-based algorithm (Maxfield et al).